PENGARUH KEAHLIAN, KONSISTENSI, DAN KONDISI KERJA TERHADAP EFISIENSI PENGGUNAAN TENAGA KERJA PADA PDAM TIRTA BINA LABUHANBATU - Muhammad Irwansyah Hasibuan (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2015)
Efficiencyis a measureif itreachesthe maximum resultswitha particulareffortgiven. Orif itreachesacertainlevel of resultswith the least effortpossiblegiven.The objective of this study is to know and to analyze the influence of expertise, consistency, and working conditions on efficiencyof employee at PDAM Tirta Bina Labuhanbatu. The method used in this study is the survey approach, the study was descriptive quantitative and the nature of the research is explanatory research. The population in this study was all employee at PDAM Tirta Bina Labuhanbatu, with the amount to 65 employees, and sample in this study all population. Data were collected by doing interviews, documentation study and giving questionnaires. Variables examined by using a likert scale. First questionnaire was tested by using the validity and reliability test. Processing data with SPSS software version 17.0 ware analyzed by using descriptive analysis an hypothesis testing with multiple linear regression.The finding in this study show that expertise, consistency, and working conditions are simultaneously significant effect of the efficiencyof employee at PDAM Tirta Bina Labuhanbatu. And partially expertise, and working conditions signicantly influence of the efficiencyof employee at PDAM Tirta Bina Labuhanbatu, and consistency no signicantly influence of the efficiencyof employee at PDAM Tirta Bina Labuhanbatu.